An Exploration of Living Experiences with post-COVID-19 in Flores, East Nusa Tenggara - Eka, Angelina Roida; Danal, Paskaliana Hilpriska; Dewi, Caludia Fariday; Bebok, Christin Florentin Meinarty (Health Information : Jurnal Penelitian, 2022)
The COVID-19 pandemic is affecting its survivors. This research aims to explore the life experiences of COVID-19 survivors in Flores, East Nusa Tenggara. The research method used was phenomenology of 10 COVID-19 survivors aged 19-39 years who had experienced COVID-19 for a maximum of 6 months at the time of data collection. Data collection used a semi-structured method and was analyzed using the Colaizzi method with ATLAS.ti software. The results of the study obtained 19 codes, 7 sub-themes and 3 themes with the main themes namely living in the shadow of COVID-19, the psychosocial burden of transmitting COVID-19, and vaccination status increasing self-confidence. There are various implications in relation to psychosocial which can be studied more deeply by further research.